Study of the Polar Arteries Supplying the Spleen and Their Significance in Its Viability - Abdulmonem Al-Hayani, Abdulmonem Al-Hayani (Journal of Rawalpindi Medical College, 2007)
Background: To study the blood supply of the spleen and its segmental distribution, with a particular interest on the presence and adequacy of collateral vessels supplying the spleen. Methods: The study was performed at the Department of Anatomy, Faculty of Medicine, King Abdul-Aziz University, Jeddah, Saudi Arabia during the years 2004- 2007. In this study, the blood supply of the spleen was studied in 15 human stillbirths and 10 adult cadavers of different ages and sexes. The study involved dissection, radiological and injection-corrosion techniques. In addition, an experimental study was carried out on twelve albino rats which were divided into 3 groups. In the first group, the splenic artery was ligated. In the second group, the terminal splenic branches were ligated and the third group was left as a control. Two weeks after ligation, the spleens from different rats were removed and examined. Results: In the human specimens, the results showed that the medial end of spleen was found to receive one or more polar arteries arising from the following sources; the upper short gastric artery (40%), both upper short gastric artery and arterial network at the stomach fundus (48%), the phrenic artery (8%) or from the aorta (4%). The lateral end of spleen was also found to receive lateral polar artery which arose in all cases from the left gastroepiploic artery. Regarding the rats, the results showed that in the first group, the spleen looked normal except in one case where an infarction was produced. In the second group, the spleen remained normal and functioning as evidenced by the maintained phagocytic activity to India ink. Conclusions: It was concluded that the spleen is supplied by polar arteries in addition to the terminal splenic branches and that arteries can maintain viable and functioning spleen even after ligation of the splenic artery or its terminal branches